High Helicobacter pylori numbers are associated with low eradication rate after triple therapy. Issue 6 (June 1995) - Moshkowitz, M; Konikoff, F M; Peled, Y; Santo, M; Hallak, A; Bujanover, Y; Tiomny, E; Gilat, T
Abstract : This study tested the influence of pretreatment bacterial density on the eradication rate of Helicobacter pylori with triple therapy. One hundred and thirty two patients with endoscopically confirmed H pylori positive, duodenal ulcer or antral gastritis were treated with triple therapy (colloidal bismuth/metronidazole/amoxicillin) for two weeks. Pretreatment urease activity was assessed by the 14C-urea breath test (UBT) in all patients. The mean (SD) pretreatment UBT concentration was similar in patients with duodenal ulcers (318.4 (175.0)) and patients with antral gastritis (288.9 (165.5)). Overall eradication of H pylori was achieved in 85 of 132 patients (64.4%), but was significantly different between patients with high, intermediate, or low pretreatment urease activity (37.5%, 69.5%, and 87.8% respectively). The mean post-treatment UBT value of patients in whom eradication failed was in direct correlation with the pretreatment UBT values. In conclusion, bacterial density, as assessed by urease activity, is an important factor in predicting H pylori eradication. It is suggested that the pretreatment UBT has the potential to identify patients who require modification of the standard therapeutic regimen.